OBSERVATIONS ON THE FREQUENCY OF INTRASEASONAL MATURITY AND BUNDH BREEDING OF LABEO ROHITA (HAM) AND CIRRHINUS MRIGALA (HAM) AT SONEPUR, ORISSA - Badapanda, H S; Das, P K; Patnaik, G C (Indian Journal of Fisheries, 2011)
During July, 1980, natural spawning of Labeo rohita (Ham) and Cirrihinusmrigala (Hani) have been observed en masse both in dry and wet bundhs for thefirst time in Orissa. The brood stock kept in distressed condition during summermonths have spawned naturally in early part of monsoon. Feeding with groundnutoil-cake at 0.5% (before spawning) and at 1.0% (after spawning) of body weightof the fishes has helped in secondary intra-seasonal maturity after a period of49 days. These gravid fish have been found to spawn naturally again in the wetbundh after a gap of 64 days. Such observations have been recorded for the firsttime in India. Topography and soil texture of the bundhs and environmentalphysico-chemical factors at the time of spawning have been discussed